Histochemical examination on principal collagen fibers in periodontal ligaments of ascorbic acid-deficient ODS-od/od rats. (3rd July 2019) - Hasegawa, Tomoka; Miyamoto-Takasaki, Yukina; Abe, Miki; Qiu, Zixuan; Yamamoto, Tomomaya; Yimin,; Yoshida, Taiji; Yoshino, Hirona; Hongo, Hiromi; Yokoyama, Ayako; Sasaki, Muneteru; Kuroshima, Shinichiro; et al.
Abstract: In this study, we aimed to clarify the role of ascorbic acid in collagen synthesis in periodontal ligaments using osteogenic disorder Shionogi (ODS)/ShiJcl- od/od rats lacking L-gulonolactone oxidase. These rats cannot synthesize ascorbic acid in vivo . Eight-week-old ODS/ShiJcl- od/od male rats were administered ascorbic acid solution at a concentration of 200 mg/dL (control group, n  = 6) or ascorbic acid solution at concentration of 0.3 mg/dL (insufficient group, n  = 12). Six rats of the insufficient group were then given with ascorbic acid solution at concentration of 200 mg/dL for additional 3 weeks (rescued group, n  = 6), and then, their mandibles were histochemically examined. Consequently, the insufficient group specimens were seen to possess fewer collagen fibers, and silver impregnation revealed numerous fine, reticular fiber-like fibrils branching off from collagen in the periodontal ligaments. In control group, faint immunoreactivities for matrix metalloproteinase (MMP)2 and cathepsin H were seen in the periphery of blood vessels and throughout the ligament, respectively. In contrast, in the insufficient group, intense MMP2-immunoreactivity was observed to be associated with collagen fibrils in the periodontal ligaments, and cathepsin H-immunopositivity was seen in ligamentous cells. The rescued group showed abundant collagen fibers filling the periodontal ligament space. Under transmission electron microscopy, ligamentous fibroblasts incorporated collagen fibrils into tubular endosomes/lysosomes while simultaneously synthesizing collagen fibril bundles. Thus, ascorbic acid insufficiency affected the immunolocalization of cathepsin H and MMP2; however, ligamentous fibroblasts appear to possess the potential to synthesize collagen fibers when supplied with ascorbic acid.